Inter-State Water Sharing in India: From Conflict to Co-operation. - Singh, Nina (2008)
The threat perception of scarcity and unjust distribution of water-a finite, pre-eminent natural resource-has made its relationship with conflict. It is an area of continued interest and debate in both the policy literature and popular press at the international level. In India too, the states are in conflict with each other on a variety of issues over sharing of inter-state river waters. The present paper attempts to explore different facets of this issue based on exhaustive literature survey. The more valuable lesson of international experience is that water is a resource whose characteristics tend to induce cooperation, and incite violence only as an exception. In India, however, the situation is different, conflict-resolution mechanisms have to be addressed from different angles. To begin with, these disputes have to be disentangled from the more general State-State conflicts, and from everyday political issues. The possibility of a National Water Commission, independent of daily political pressures, should be explored. River water resources require sustainable integrated planning for larger ecological systems of which rivers are a part, by way of State-State cooperation and extending beyond centralised technology-driven planning.